2006
DOI: 10.1002/jlcr.1066
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical characterisation of99mTc-tin fluoride colloid agent used for labelling white cells

Abstract: Tc-tin fluoride colloid is an agent used to label leucocytes, for the imaging and diagnosis of inflammatory conditions including Crohn's disease. Despite previous investigations, this radiolabelling agent is still poorly characterised. The aim of this work was to examine the process of formation and stability of 99m Tc-tin fluoride colloid using mass spectrometry, membrane filtration and atomic absorption spectrophotometric techniques. Tin-oxide bonds in tin clusters were identified in the stannous fluoride re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…In the absence of NaF and the 0.2 µm filtration step, the pilot reactions afforded large 67 Ga‐ h ‐SnF 2 particles, although these were not characterised above 3 µm. There was no obvious effect when low levels of NaF in 0.06–0.12 mg were present in the reaction mixture, but the radiolabelling efficiency was inhibited above 0.62 mg. As a comparison, it was previously shown that 5 mg NaF in the reaction vial did not inhibit 99m Tc‐ h ‐SnF 2 colloid formation at room temperature . For 67 Ga‐ h ‐SnF 2 particles at 100 °C though, this excipient interfered with 67 Ga‐coordination because 100% of soluble 67 Ga‐ions were detected in the neutralised formulation.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…In the absence of NaF and the 0.2 µm filtration step, the pilot reactions afforded large 67 Ga‐ h ‐SnF 2 particles, although these were not characterised above 3 µm. There was no obvious effect when low levels of NaF in 0.06–0.12 mg were present in the reaction mixture, but the radiolabelling efficiency was inhibited above 0.62 mg. As a comparison, it was previously shown that 5 mg NaF in the reaction vial did not inhibit 99m Tc‐ h ‐SnF 2 colloid formation at room temperature . For 67 Ga‐ h ‐SnF 2 particles at 100 °C though, this excipient interfered with 67 Ga‐coordination because 100% of soluble 67 Ga‐ions were detected in the neutralised formulation.…”
Section: Discussionmentioning
confidence: 89%
“…In this case, it is not clear if acetic acid acts as a neutral donor molecule and/or replaces some fluoride ions during the hydrolysis of Sn 2+ . This result suggested that water is still an important donor molecule, not only to form stannous oxyfluoride, SnO.SnF 2 · 3H 2 O, Sn 2 OF 2 · xH 2 O (x = 0, 3, 4, 6) and 3SnO.2SnF 2 · 6H 2 O, but also to provide oxygen atoms that link with tin atoms in the particle structure.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations